The Impact of the Covid-19 Pandemic on Student Learning Activities at Madrasah Ibtidaiyah - Suhaimi, Suhaimi; Saidah, Saidah; Rahman, Rashid; Idris, Haziq (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
Current technological developments have produced many applications that can be used as learning methods for educators for online learning during the pandemic. One application that can be used is Telegram. Telegram is an application as a practical message sending facility, which has a high level of security, and can transfer large files. The purpose of this study is to develop a technological learning method for educators so that educators are assisted in carrying out their duties to deliver fiqh learning materials to students as an online learning medium. The research method used by the researcher is the quantitative method. This method uses Google Form as a form of survey to educators and students in utilizing Telegram as an online learning medium in the subject of Fiqh. The results of this study illustrate that Telegram is one application that can be utilized for online learning because it can accommodate large files such as learning videos. The conclusion of this study explains that the Telegram application can help educators and students in online learning in the subject of Fiqh. The limitation of this study is that the researcher only conducted research on the utilization of the Telegram application in the subject of Fiqh, the researcher hopes that further researchers can conduct research on other subjects.